2021
DOI: 10.1186/s13019-021-01588-7
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary team nursing model in the treatment of patients undergoing transapical mitral valve clamping: a prospective study

Abstract: Background As a new surgical method for older adults with cardiac insufficiency, transapical mitral valve clamp surgery requires the cooperation of practitioners across multiple disciplines to ensure appropriate treatment and nursing care. This study aimed to explore the utility of a multidisciplinary team nursing model in the clinical treatment and nursing care of patients undergoing transapical mitral valve clamping. Methods Our sample of ten pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Postoperative pain leads to the re ex contraction of the abdominal and chest muscles. Meanwhile, postoperative pain limits coughing, inducing poor sputum excretion, atelectasis, and secondary pulmonary infection and consequently aggravating the degree of hypoxia [17]. Effective analgesia can reduce postoperative complications, promote early postoperative activities, shorten the length of hospital stay, and speed up postoperative recovery.…”
Section: Postoperative Pain Carementioning
confidence: 99%
“…Postoperative pain leads to the re ex contraction of the abdominal and chest muscles. Meanwhile, postoperative pain limits coughing, inducing poor sputum excretion, atelectasis, and secondary pulmonary infection and consequently aggravating the degree of hypoxia [17]. Effective analgesia can reduce postoperative complications, promote early postoperative activities, shorten the length of hospital stay, and speed up postoperative recovery.…”
Section: Postoperative Pain Carementioning
confidence: 99%
“…Previous studies have found that strengthening the nursing cooperation of children during appendicitis operation can significantly improve children's rehabilitation, reduce the stress caused by surgery, and improve the sleep quality [7,8,9]. Integrated rapid rehabilitation is a new nursing model which is recognized at home and abroad, and can effectively contribute to the process of disease rehabilitation [10]. On the basis of previous studies, this study utilized LA to treat children with appendicitis, and observed and analyzed the effects of different nursing modes on perioperative indices, pain degree, stress response, and quality of life of children with appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…(Muhith, 2016) Thus, those aspects should be considered in the management of health service system.(S. Li et al, 2021) This success is affected by several factors either from nurse or system built in the hospital. (Prawirodihardjo, 2019) The supervision, leadership authority character, and compliance of nursing team member affect patient nursing quality.…”
Section: Introductionmentioning
confidence: 99%